Uterine Perforation as a Complication After Unsafe Abortion: Serial Case - I Made Darmayasa; Nicholas Renata Lazarosony (JURNAL KESEHATAN REPRODUKSI, 2021)
The demand for abortion and the incidence of unsafe abortion are still very high. About 45% of all abortions worldwide are unsafe abortions. Unsafe abortion is still a public health problem and one of the causes of maternal morbidity and mortality. In this article, we report 2 cases of uterine perforation after provocation or induced abortion due to unwanted pregnancy. The diagnosis of uterine perforation was established by clinical suspicion and exploratory laparotomy. Many factors affect access to abortion and one of them is the law regarding abortion. Countries with almost no deaths from unsafe abortions are countries that allow abortion on demand without restrictions. Meanwhile, unsafe abortion can be prevented through prevention and controlKeywords: unsafe abortion, uterine perforation.